Introductory algebra - Strnad, Wayne A. (Boston : Prindle, Weber & Schmidt, 1987)
"From a mathematical point of view, this book covers all the needed material for what is generally classified as Introductory Algebra. A basic knowledge of arithmetic is the only prerequisite. This text will also help students understand the material present on the General Educational Development (GED) exam."
Includes appendices and index.
English text.